2023
DOI: 10.1017/qut.2023.4
|View full text |Cite
|
Sign up to set email alerts
|

The state of quantum computing applications in health and medicine

Abstract: Quantum computing hardware and software have made enormous strides over the last years1. Questions around quantum computing’s impact on research and society have changed from “if” to “when/how”. The 2020s have been described as the “quantum decade”, and the first production solutions that drive scientific and business value are expected to become available over the next years. Medicine, including fields in healthcare and life sciences, has seen a flurry of quantum-related activities and experiments in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Since its original proposal by Richard Feinman [ 18 ], quantum computing has evolved from a concept to a practical technology [ 19 ] which is now being actively utilised with the potential to solve some of the more complex problems. These probably fall into the following three categories: (1) simulating nature - including chemistry, materials science, and physics; (2) processing data with a complex structure - including artificial intelligence/machine learning (AI/ML), factoring, and ranking; and (3) search and optimization - including pricing, risk analysis, and sampling [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its original proposal by Richard Feinman [ 18 ], quantum computing has evolved from a concept to a practical technology [ 19 ] which is now being actively utilised with the potential to solve some of the more complex problems. These probably fall into the following three categories: (1) simulating nature - including chemistry, materials science, and physics; (2) processing data with a complex structure - including artificial intelligence/machine learning (AI/ML), factoring, and ranking; and (3) search and optimization - including pricing, risk analysis, and sampling [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent detailed review of quantum computer literature associated with the medical sciences [ 20 ] detailed three broad areas that most studies fit into, which include genomics and clinical research, diagnostics, and treatments and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple germane reviews exist, focusing on the computational biology perspective 13,14,15,16,17,18 . In addition to pharmaceutical and life sciences uses 19 , clinical applications and medical use cases are now coming increasingly into the picture 20 . The present chapter focuses on three key use case areas associated with (precision) medicine (Figure 3).…”
Section: Applying Quantum Computing In Medicinementioning
confidence: 99%
“…Previous studies have demonstrated the effectiveness of various AI techniques in distinguishing (and grading) LGGs from HGGs by using molecular markers such as IDH, TP53, and ATRX mutation status; the presence of 1p/19q codeletion; MGMT promoter methylation status; and other molecular attributes and clinical features [13,26]. On the other hand, classical AI approaches encounter constraints attributed to factors such as data quality and noise, feature dimensionality, intricate relationships among features, and the dimension of the classical vector space [47,48]. The diagnosis and treatment results are affected by these situations.…”
Section: Introductionmentioning
confidence: 99%